Effect of fibroblast and platelet-derived growth factors on co-culture of human gingival fibroblasts and umbilical vein endothelial cells - Allah, Nasar Um Min (2018)
Numerous types of single cells in in-vitro cultures have been studied in tissue engineering, but the study on direct paracrine interactions between heterotypic cells population is lacking. Co-culture approach establishes an excellent atmosphere to study these interactions. The objective of this in-vitro experimental study was to determine the effects of fibroblast and platelet-derived growth factor ((FGF-2 and PDGF-BB) in a co-culture of human gingival fibroblasts (HGFs) and human umbilical vein endothelial cells (HUVECs). To this end, the medium for the establishment of monolayer and co-culture of these cells were first optimised. Thereafter, the optimal concentrations of these growth factors were determined in a monolayer and then in a co-culture medium by assessing the cell viability using MTT assay. Next, gene expression analysis for fibroblast and angiogenic biomarkers was assessed using realtime RT-PCR to study the stimulatory effect of these growth factors by using 6 wellplate with transwell inserts. Afterwards, statistical analysis of the results was performed using one-way ANOVA and Kruskal-Wallis test with p < 0.05 considered statistically significant. Results of cell viability assay showed that the effect of FGF-2 on HGF was dose-dependent and was optimum at a concentration of 5 ng/ml (p =0.001), while that of PDGF-BB on HUVEC was optimum at a concentration of 20 ng/ml (p =0.004). The stimulatory effect of FGF-2 and PDGF-BB on HGF and HUVEC was supported by the real-time RT-PCR results which showed that there is a significant upregulation (p < 0.05) of gene biomarkers in the treatment group of bothcells after three days of co-culture experiment, compared to control group. Therefore, it is concluded that there is the possibility of a synergistic effect of these two growth factors on a co-culture of HGF and HUVEC which were suggestive of a proangiogenic activity.